Language on display : writers, fiction and linguistic culture in post-Soviet Russia - Lunde, Ingunn, 1969- (Edinburgh University Press, 2018)
Post-Soviet Russia was a period of linguistic liberalisation, instability and change with varied attempts to regulate and legislate language usage. This book looks at how these debates featured in literature and illustrates the discussion through six interpretive readings of post-Soviet Russian prose.
Keywords: Die Stadt ohne Juden; Linguistic change -- Russia (Federation); Language and culture -- Russia (Federation); Linguistics -- Russia (Federation); Sociolinguistics -- Russia (Federation); Changement linguistique -- Russie.; Langage et culture -- Russie.; Linguistique -- Russie.; Sociolinguistique -- Russie.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; BIOGRAPHY & AUTOBIOGRAPHY -- General.; Language and culture; Linguistic change; Linguistics; Sociolinguistics; Russia (Federation); Literatur; Sprache -- Motiv; Sprachwandel; Soziolinguistik; Sprache; Sprachpflege; Kultur; Russland